2014
DOI: 10.1128/aac.03608-14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Salmonella enterica Serovar Typhi Isolates from Bangladesh, Indonesia, Taiwan, and Vietnam

Abstract: We characterized Salmonella enterica serovar Typhi isolates from Bangladesh, Indonesia, Taiwan, and Vietnam to investigate their genetic relatedness and antimicrobial resistance. The isolates from Bangladesh and Vietnam were genetically closely related but were distant from those from Indonesia and Taiwan. All but a few isolates from Indonesia and Taiwan were susceptible to all antimicrobials tested. The majority of isolates from Bangladesh and Vietnam were multidrug resistant (MDR) and belonged to the widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 35 publications
9
58
6
2
Order By: Relevance
“…Long-read sequencing of 2012 Indian isolate ERL12960 ( Supplementary Table 4 ) confirmed that the entire MDR locus, flanked by copies of IS 1 , was integrated at this location near cyaA (Fig. 5), in agreement with other recent reports 15,16 . The nucleotide sequence was identical to that in the IncHI1-PST6 plasmid of H58 isolate 10425_1_48_Viety3-193_1997, which we also sequenced for comparison.…”
Section: Resultssupporting
confidence: 89%
“…Long-read sequencing of 2012 Indian isolate ERL12960 ( Supplementary Table 4 ) confirmed that the entire MDR locus, flanked by copies of IS 1 , was integrated at this location near cyaA (Fig. 5), in agreement with other recent reports 15,16 . The nucleotide sequence was identical to that in the IncHI1-PST6 plasmid of H58 isolate 10425_1_48_Viety3-193_1997, which we also sequenced for comparison.…”
Section: Resultssupporting
confidence: 89%
“…SGI11-carrying S. Typhi strains may have the advantage in the face of antimicrobial exposure, and whether the strains are more capable of spreading needs further investigation. Notably, 11 of the 18 MDR S. Typhi isolates from Bangladesh analyzed in this study have developed resistance to high-level fluoroquinolone by alterations in gyrase A (S83F and D87G) and enhanced efflux pumps (9). High-level fluoroquinolone resistance on salmonellae may have a prohibitive fitness cost (29); however, fluoroquinolone-resistant S. Typhi strains may have a fitness benefit even in the absence of antimicrobial pressure (30).…”
mentioning
confidence: 96%
“…In a previous study, we characterized 38 S. Typhi isolates collected in Bangladesh in 2007 and revealed that 68% of the isolates were MDR, 82% were resistant to nalidixic acid (Na), and 39% were resistant to ciprofloxacin (Cp) (9). The 26 MDR isolates were resistant to 5 to 7 antimicrobials (ampicillin, chloramphenicol, ciprofloxacin, nalidixic acid, streptomycin [S], sulfamethoxazole [Su], tetracycline [T], and trimethoprim [Tm]) and were grouped into 7 resistance patterns, A2 (11 isolates resistant to ACCpNaSSuTm), A3 (1 resistant to ACpNaSSuT), A4 (3 resistant to ACpNaSuT), A5 (2 resistant to ACNaSSuTTm), A6 (6 resistant to ACNaSSuTm), A9 (2 resistant to ACSSuTTm), and A11 (1 resistant to ACSSuTm).…”
mentioning
confidence: 99%
“…In a report from Bangalore, India, only 3 out of 50 (6%) S. Typhi or S. Paratyphi A isolates were susceptible to ciprofloxacin; 38 out of 50 (76%) of these isolates were resistant to nalidixic acid, indicating the presence of a QRDR mutation, and only 7 (14%) were ciprofloxacin intermediate and nalidixic acid susceptible (31). Such data suggest that FQs have already been lost as a useful therapeutic option for many patients with enteric fever in parts of India, as well as Bangladesh (32) and Pakistan (33).…”
Section: Low-level Fq Resistance Is Associated With Poorer Clinical Omentioning
confidence: 99%